The performance analysis of outdoor wireless network using quality of services method: A case study EFTENET network laboratory of Universitas Muhammadiyah Magelang - Agus Susanto; Purwono Hendradi; Setiya Nugroho (Borobudur Informatics Review, 2021)
At present many of the clients connected in EFTENET still experience problems in delays in sending data when accessing data communication services. Therefore, a study was conducted to look at the performance of EFTENET's outdoor wireless services with the Quality of service method. The parameters used to measure are bandwidth, delay, packet lost and jitter which are then compared with the standardization version of Telecommunications and Internet Protocol Harmonization Over Network. From the results of the study concluded that outdoor wireless networks EFTENET has the category of "GOOD" degradation in the parameters of bandwidth, delay, jitter and geographical conditions between the transmitter and client. Data transmission delay occurs because the value of packet lost has the value of the "MEDIUM" degradation category. The value of packet lost is affected by a fairly high noise condition between the transmitter point and receiver so that the transmitted data is not received optimaly.